Pengembangan Keberbakatan dan Minat Siswa dalam Konteks Pendidikan - Habsy, Bakhrudin All; Lena, Annora Malva; Aryanti, Dwi Wulan; Asfinda, Hany (TSAQOFAH, 2024)
The analysis that we make this time aims to develop students' giftedness, which the term gifted itself can be described by Plato as Men of gold or "golden men", namely someone who has a superior intellectual character, then translated from the English word gifted, which others are giftedness, talented, talented, creative, insightful, genius and precocious. So what is meant by a gifted person is a person who has a high level of intelligence, judging from the scores obtained from intelligence tests. Two approaches to looking at talent, namely one-dimensional and multidimensional, namely the intelligence dimension and various other measures. And gifted models are (a) genetically oriented, (b) cognitive models, (c) achievement-oriented, and (d) systemic models. The development of student giftedness is someone from the chronological age range in the age range of 12-18 years, and is undergoing psychosocial changes related to identity, independence, friendship, sexuality and achievement, and has a general ability or intelligence above average, high creativity, and commitment to duty.